ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU KELAPA PADA INDUSTRI TEPUNG KELAPA (Studi Kasus Pada PT. Royal Coconut) - Anggi Lisli Montolalu; Celcius ., Talumingan; Eyverson ., Ruauw (AGRI-SOSIOEKONOMI, 2016)
The purpose of this research is to analyzed the coconut supply in coconut flour industry (case study at PT. Royal Coconut). This research conducted for three months, February 2016 to April 2016. The data used in this research are prime and secondary data. Prime data obtained by interview with the head manager of the company, the secondary data obtained from company archives, data from BPS, the Department of Industry and Commerce of North Sulawesi, previous literatures and internet. Data processed by EOQ method. The result showed that the raw material supply control policy by PT. Royal coconut not efficient. This shown by the company supply cost higher than the analysis result by used EOQ method with the optimum amount of coconut each order by EOQ method is 384.347,44 kg with total economic inventory cost Rp. 12.310.648.*ls